Curcumin extract for prevention of type 2 diabetes - Somlak Chuengsamarn (2018)
OBJECTIVE - To assess the efficacy of curcumin in delaying development of type 2 diabetes mellitus (T2DM) in the prediabetic population. RESEARCH DESIGN AND METHODS - This randomized, double-blinded, placebo-controlled trial included subjects (n = 240) with criteria of prediabetes. All subjects were randomly assigned to receive either curcumin or placebo capsules for 9months. To assess the T2DM progression after curcumin treatments and to determine the number of subjects progressing to T2DM, changes in β-cell functions (homeostasis model assessment [HOMA]-β, C-peptide, and proinsulin/insulin), insulin resistance (HOMA-IR), anti-inflammatory cytokine (adiponectin), and other parameters were monitored at the baseline and at 3-, 6-, and 9-month visits during the course of intervention. RESULTS - After 9 months of treatment, 16.4% of subjects in the placebo group were diagnosed with T2DM, whereas none were diagnosed with T2DM in the curcumin-treated group. In addition, the curcumin-treated group showed a better overall function of β-cells, with higher HOMA-β (61.58 vs. 48.72; P < 0.01) and lower C-peptide (1.7 vs. 2.17; P < 0.05). The curcumin-treated group showed a lower level of HOMA-IR (3.22 vs. 4.04; P < 0.001) and higher adiponectin (22.46 vs. 18.45; P < 0.05) when compared with the placebo group. CONCLUSIONS - A 9-month curcumin intervention in a prediabetic population significantly lowered the number of prediabetic individuals who eventually developed T2DM. In addition, the curcumin treatment appeared to improve overall function of β-cells, with very minor adverse effects. Therefore, this study demonstrated that the curcumin intervention in a prediabetic population may be beneficial. © 2012 by the American Diabetes Association.